Mutant alleles associated with late-onset ornithine transcarbamylase deficiency in male patients have recurrently arisen and have been retained in some populations - Numata, Sanae; Koda, Yoshiro; Ihara, Kenji; Sawada, Tomo; Okano, Yoshiyuki; Matsuura, Toshinobu; Endo, Fumio; Yoo, Han-Wook; Arranz, Jose A; Rubio, Vicente; Wermuth, Bendicht; Ah Mew, Nicholas; et al. (Journal of human genetics, 2010)
We performed haplotype analysis using nine single nucleotide polymorphisms in the ornithine transcarbamylase gene to explore the ancestral origins of three mutations associated with late-onset phenotype in male patients: p.R40H, p.R277W and p.Y55D. Overall, 8 haplotypes were defined among 14 families carrying p.R40H, 5 families carrying p.R277W and 2 families with p.Y55D mutations. Of nine Japanese families carrying p.R40H, eight exhibited haplotype (HT)1, whereas the other family harbored HT2. Among three Caucasian families, one Spanish and one Australian family bore HT3; one Austrian family had HT4. Two US patients harbored HT2 and HT4. Among families carrying p.R277W, HT5 was found in one Japanese, one Korean and one US family. Two other US families had HT2 and HT6. Two families carrying p.Y55D, both Japanese, shared HT1. These results indicate that the p.R40H mutation has arisen recurrently in all populations studied, although there is evidence for a founder effect in Japan, with most cases probably sharing a common origin, and to a lesser extent in subjects of European ancestry (HT3). It is evident that p.R277W mutation has recurred in discrete populations. The p.Y55D mutation appears to have arisen from a common ancestor, because this transversion (c.163T>G) occurs rarely.